Membangun Budaya Literasi Sejak Dini Kunci Generasi Cerdas - Zakiya, Nida; Mas’odi, Mas’odi; Millah, Ana Qoimatul; Khumairah, Anis (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Literacy is not limited to the ability to read and write, but also includes the skills to understand information, think critically, and express ideas effectively. Developing a culture of literacy from an early age is essential as a foundation for shaping a smart generation that is ready to face the challenges of a changing world. The closest environments—family, school, and community—play a key role in this process. The purpose of this writing is to highlight the urgency of instilling a culture of literacy from an early age and to describe the strategic roles of families, educational institutions, and social environments in fostering a competent and competitive generation. Based on a literature review of various studies conducted in the past five years, it is evident that the roles of the family, school, and community are crucial in nurturing children's literacy culture. This article adopts a descriptive qualitative approach using the literature review method. The analysis results indicate that early literacy has a significant impact on children's cognitive, social, and emotional development. The success of character formation in children's literacy is strongly influenced by the active roles of families, schools, and communities. Parents serve as primary role models, teachers act as inspirational learning facilitators, and the community, through institutions such as community reading centers (Taman Bacaan Masyarakat or TBM), provides access and literacy activities that holistically support children's character development